Deterioration Model of Soil Slopes - ZAINUDIN, SITI AQILAH (Universiti Teknologi PETRONAS, 2018)
Soil is in fact an extremely complex, variable and living medium that regulates our environment and responds to the pressures imposed upon it. Based on Qasim et al., (2013) they explains that although Malaysia is not a precipitous country because in Malaysia only consists of less than 25% of mountains and hills in the terrain, however, slope failure is frequent. These types of disaster have caused considerable numbers of death, destruction of properties loss and immerse direct and indirect economic losses. Planning, monitoring, design, construction and maintenance are very important to achieve a safe and cost-effective hill-site development (Rahman and Mapjabil, 2017). In this paper, deterioration of soil slope and slope stability analysis was studied. The factor of affecting the deterioration of soil slopes and how ages of the slope may affect the slope stability has been discussed in this paper.